Reputation: 1724
I was trying to recreate a simplified version of the natural numbers, for learning purposes (as it involves inductive definitions, recursive functions, etc...). In that process however, I got stuck in something that I thought would be very trivial.
Basically, I have a definition for natural numbers 'natt
' and a definition for the '<
' relation:
datatype natt = Zero | Succ natt
primrec natt_less :: "natt ⇒ natt ⇒ bool" (infixl "<" 75) where
"natt_less n Zero = False"
| "natt_less n (Succ m') = (case n of Zero ⇒ True | Succ n' ⇒ natt_less n' m')"
and from these, I tried to prove 3 basic properties of the <
relation:
~ (a < a)
a < b ⟹ ~ (b < a)
a < b ⟹ b < c ⟹ a < c
I was able to prove the first, but not the others. What took me even more by surprise, is that there are some sub-lemmas that would aid on these, such as Succ a < b ⟹ a < b
, a < b ⟹ a < Succ b
or a < b ∨ a = b ∨ b < a
, which seem even more trivial, but nonetheless I was also not able to prove, even after many attempts. It seems like only one of these (including 2.
and 3.
) is enough to prove the rest, but I wasn't able to prove any of them.
I'm mostly trying to use induction. Together with the fact that I've made the definitions myself, there are two possibilities - Either my definitions are wrong, and do not have the desired properties, or I'm missing some method/argument. So, I have two questions:
<
and lacks the desired properties)? If so, how may I fix it?For context, my current attempts are by induction, which I can prove the base case, but always get stuck in the induction case, not really knowing where to go with the assumptions, such as in this example:
lemma less_Succ_1: "Succ a < b ⟹ a < b"
proof (induction b)
case Zero
assume "Succ a < Zero"
then have "False" by simp
then show ?case by simp
next
case (Succ b)
assume "(Succ a < b ⟹ a < b)" "Succ a < Succ b"
then show "a < Succ b" oops
Upvotes: 0
Views: 175
Reputation: 1724
After some tips from user9716869, it's clear that my main problem was the lack of knowledge about the arbitrary
option in induction
. Using (induction _ arbitrary: _)
and (cases _)
(see the reference manual for details), the proofs are quite straight forward.
Since these are made for educational purposes, the following proofs are not meant to be concise, but to make every step very clear. Most of these could be vastly reduced if more automation is desired, and some can be done in one line (which I left as a comment below the lemma).
Note: In these proofs, we are using an implicit lemma about inductive types, their injectivity (which implies (Succ a = Succ b) ≡ (a = b)
and Zero ≠ Succ a
). Furthermore, (Succ a < Succ b) ≡ (a < b)
by definition.
First, we prove 2 useful lemmas:
a < b ⟹ b ≠ Zero
b ≠ Zero ⟷ (∃ b'. b = Succ b')
lemma greater_not_Zero [simp]: "a < b ⟹ b ≠ Zero"
(*by clarsimp*)
proof
assume "a < b" "b = Zero"
then have "a < Zero" by simp
then show "False" by simp
qed
lemma not_Zero_is_Succ: "b ≠ Zero ⟷ (∃ b'. b = Succ b')"
(*by (standard, cases b) auto*)
proof
show "b ≠ Zero ⟹ ∃ b'. b = Succ b'"
proof (cases b)
case Zero
assume ‹b ≠ Zero›
moreover note ‹b = Zero›
ultimately show "∃b'. b = Succ b'" by contradiction
next
case (Succ b')
assume ‹b ≠ Zero›
note ‹b = Succ b'›
then show "∃b'. b = Succ b'" by simp
qed
next
assume "∃ b'. b = Succ b'"
then obtain b'::natt where "b = Succ b'" by clarsimp
then show "b ≠ Zero" by simp
qed
Armed with these, we can prove the 3 main statements:
~ (a < a)
a < b ⟹ ~ (b < a)
a < b ⟹ b < c ⟹ a < c
lemma less_not_refl [simp]: "¬ a < a"
(*by (induction a) auto*)
proof (induction a)
case Zero
show "¬ Zero < Zero" by simp
next
case (Succ a)
note IH = ‹¬ a < a›
show "¬ Succ a < Succ a"
proof
assume "Succ a < Succ a"
then have "a < a" by simp
then show "False" using IH by contradiction
qed
qed
lemma less_not_sym: "a < b ⟹ ¬ b < a"
proof (induction a arbitrary: b)
case Zero
then show "¬ b < Zero" by simp
next
case (Succ a)
note IH = ‹⋀b. a < b ⟹ ¬ b < a›
and IH_prems = ‹Succ a < b›
show "¬ b < Succ a"
proof
assume asm:"b < Succ a"
have "b ≠ Zero" using IH_prems by simp
then obtain b'::natt where eq: "b = Succ (b')"
using not_Zero_is_Succ by clarsimp
then have "b' < a" using asm by simp
then have "¬ a < b'" using IH by clarsimp
moreover have "a < b'" using IH_prems eq by simp
ultimately show "False" by contradiction
qed
qed
lemma less_trans [trans]: "a < b ⟹ b < c ⟹ a < c"
proof (induction c arbitrary: a b)
case Zero
note ‹b < Zero›
then have "False" by simp
then show ?case by simp
next
case (Succ c)
note IH = ‹⋀a b. a < b ⟹ b < c ⟹ a < c›
and IH_prems = ‹a < b› ‹b < Succ c›
show "a < Succ c"
proof (cases a)
case Zero
note ‹a = Zero›
then show "a < Succ c" by simp
next
case (Succ a')
note cs_prem = ‹a = Succ a'›
have "b ≠ Zero" using IH_prems by simp
then obtain b' where b_eq: "b = Succ b'"
using not_Zero_is_Succ by clarsimp
then have "a' < b'" using IH_prems cs_prem b_eq by simp
moreover have "b' < c" using IH_prems b_eq by simp
ultimately have "a' < c" using IH by simp
then show "a < Succ c" using cs_prem by simp
qed
qed
Upvotes: 0